2022
DOI: 10.3390/atmos13101675
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Particle Sizers and Counters with Soot-like, Salt, and Silver Particles

Abstract: Vehicle emission regulations in Europe and many Asian countries include a particle number limit. The number concentration is measured, typically, with condensation particle counters (CPCs). For research purposes, the size distributions provide useful information. Scanning mobility particle sizers (SMPSs) accurately provide the size distribution but are not suitable for transient aerosol. Engine (fast) exhaust particle sizers (EEPSs) cover this gap, but with less accuracy. Fast size distribution instruments are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 89 publications
1
6
0
Order By: Relevance
“…Differences in the counting efficiencies in the cut-off curve have been reported by many researchers testing in the single counting mode [49][50][51]. These findings justify why there were no differences of the material in the plateau region (25 to 50 nm range) in the photometric mode for graphite, soot, and salt particles in our previous study [14].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Differences in the counting efficiencies in the cut-off curve have been reported by many researchers testing in the single counting mode [49][50][51]. These findings justify why there were no differences of the material in the plateau region (25 to 50 nm range) in the photometric mode for graphite, soot, and salt particles in our previous study [14].…”
Section: Discussionsupporting
confidence: 81%
“…In theory, once calibrated, the photometric mode should remain in acceptable levels of accuracy (±20%) independently of the original type of particles, because all particles grow in similar sizes in the micrometer range before detection and they should have the same refractive index due to the condensed vapor of the working fluid. However, recently we found that small silver particles were underestimated at least 40% compared to soot particles [14]. There are not many studies that have examined the photometric mode range of CPCs, and even less any size dependency [15].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…It allowed for the measurement of particles in the diameter range from 5.6 nm to 560 nm (in this study, particles > 23 nm were counted). Note that EEPS uncertainty is higher than particle counters and that volatiles are also measured [43]. Technical data of the TSI 3090 EEPS analyzer are provided below (Table 3).…”
Section: Measurement Equipment For Road Testsmentioning
confidence: 99%
“…In this method, the solid particles of the aerosol are enlarged by dissipating liquid butanol first. Then the particles pass by laser light and light-sensing optics in a detection chamber [ 9 ]. The passing of the enlarged particles causing discontinuity in the laser detection of the optics, allowing the particle count to be determined.…”
Section: Introductionmentioning
confidence: 99%